2008
DOI: 10.1007/s10826-008-9190-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-Divorce Maternal Disclosure and the Father–Adolescent Relationship: Adolescent Emotional Autonomy and Inter-Reactivity as Moderators

Abstract: Utilizing longitudinal data from a project that examined the post-divorce lives of mothers and adolescents, we addressed two questions: (a) Does exposure to negative maternal disclosure about the ex-husband/father impact adolescents' perceptions of the father-adolescent relationship? and (b) Are adolescents with low emotional autonomy and high emotional inter-reactivity especially vulnerable? Participants were 154 adolescents, who ranged in age from 12 to 18 years at wave two. Although there was no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
6
3
Order By: Relevance
“…Custodial mothers had the ability and potential to share sensitive information about the father when communicating with their children.Yet, such communicational behaviour, although found in previous studies (Kenyon & Koerner 2008), was not reported by the research participants.…”
Section: Communication About the Fathers' Conductcontrasting
confidence: 67%
See 3 more Smart Citations
“…Custodial mothers had the ability and potential to share sensitive information about the father when communicating with their children.Yet, such communicational behaviour, although found in previous studies (Kenyon & Koerner 2008), was not reported by the research participants.…”
Section: Communication About the Fathers' Conductcontrasting
confidence: 67%
“…In order to insure the children's well-being and good relationship with their fathers, participants maintain a positive father image. This communication pattern contradicts the images of divorced mothers found in literature inciting their children against the father (Laakso 2004) or using their children as confidants and emotional aides (Kenyon & Koerner 2008).…”
Section: Positive Father Imagecontrasting
confidence: 67%
See 2 more Smart Citations
“…Literature has demonstrated that children and adolescents vary as to their vulnerability to the effects of marital conflict (Heatherington and Stanley-Hagan, 1999; Kenyon and Koerner, 2008). Negative life events – in which we might include also separation/divorce with high conflict – may trigger psychological stress which can also be influenced by individual factors, including self-esteem (Plancherel et al, 1997).…”
Section: Introductionmentioning
confidence: 99%